The future of tourism: evolution and future of scenario planning and strategic foresight in tourism with Albert Postma - Stefan Hartman; Albert Postma (Journal of Tourism Futures)
Purpose – As the Journal of Tourism Futures celebrates its 10th Anniversary, Dr Stefan Hartman (head of department at the European Tourism Futures Institute, NHL Stenden University of Applied Sciences) interviews Prof. Albert Postma, professor of Strategic Foresight and Scenario Planning) about Evolution and Future of Scenario Planning. Design/methodology/approach – A personal interview held on September 12, 2024. Findings – Albert Postma highlights the importance of scenario planning and strategic foresight and its evolution. Postma explains how he is taking a leading role in improving the impact of applications of scenario planning and strategic foresight in tourism practice. Originality/value – The interview provides insights into the directions of scenario planning and strategic foresight applications in tourism practice and promising pathways for future academic contribution to the Journal of Tourism Futures.